Head stereotypies in STXBP1 encephalopathy. (13th June 2013) - Kim, Young Ok; Korff, Christian M; Villaluz, Mel Michel G; Suls, Arvid; Weckhuysen, Sarah; De, Peter; Scheffer, Ingrid E
<x xml:space="preserve">Abstract</x> STXBP1 encephalopathy is associated with a range of movement disorders. We observed head stereotypies in three patients. These comprised a slow (<1Hz), high‐amplitude, horizontal, 'figure‐of‐eight' pattern, beginning at age 4–6 years and resulting in neck muscle hypertrophy, in two males; a faster (2–3Hz), side‐to‐side, 'no' movement, starting at the age of 9 years 6 months was observed in one female. Upper limb and truncal stereotypies and vocalization occurred intermittently with the head movements. The stereotypies increased with excitement but settled with concentration and sleep. Head and upper limb stereotypies are valuable clinical clues to the diagnosis of STXBP1 encephalopathy in patients with profound impairments.